H3PO4 incorporated microporous hydrogel frameworks for intermediate temperature proton exchange membrane fuel cells. (April 2015) - Li, Z.; Liu, L.; Yin, Y.; Feng, D.
<x content-type="archive" xml:space="preserve">Abstract</x> Microporous polyacrylamide/chitosan (PAAm/CS) matrix is employed as a placeholder for proton conductor H3PO4 benefiting from the adsorption of hydrogel material to H3PO4 aqueous solution. Prior to fabrication, closed microporous structure of PAAm/CS matrix is opened by a freeze drying process, following by being immersed three-dimensional PAAm/CS in concentrated H3PO4 aqueous solutions. Anhydrous H3PO4 incorporated PAAm/CS membranes are obtained after a dehydration process, which are used as intermediate-temperature proton exchange membranes (PEMs). The microporous structure, loading of H3PO4, proton conductivity, electrochemical behaviors, and fuel cell performances are systematically evaluated. Due to high H3PO4 loading in per volume unit of PEM and rapid proton migration, an impressive proton conductivity as high as 0.173 S cm−1 at 165°C under anhydrous condition is recorded. A fuel cell using a thick PEM shows a peak power density of 615 mW cm−2 with O2 and H2 as the oxidant and fuel respectively.